Randomized Controlled Trial of Extended Perioperative Counseling in Enhanced Recovery After Colorectal Surgery. Issue 6 (June 2018) - Forsmo, Håvard Mjørud; Erichsen, Christian; Rasdal, Anne; Tvinnereim, Jon Meyer; Körner, Hartwig; Pfeffer, Frank
Abstract : BACKGROUND: Enhanced recovery after surgery programs reduce the length of hospital stay in patients who undergo elective colorectal resection, but the reasons for this reduction are not well understood. OBJECTIVE: The aim of this randomized controlled trial was to assess the impact of extended perioperative counseling in treatment groups that were otherwise the same with respect to enhanced recovery after surgery criteria. DESIGN: Patients eligible for open or laparoscopic colorectal resection were randomly assigned to extended counseling (repeated information and guidance by a dedicated nurse) or standard counseling. SETTINGS: This study was conducted at a single institution. PATIENTS: Patients (n = 164) were randomly assigned to enhanced recovery after surgery plus extended counseling (n = 80) or enhanced recovery after surgery with standard counseling (n = 84). MAIN OUTCOME MEASURES: The primary end point was the total length of hospital stay. Discharge criteria were defined. Secondary end points were postoperative complications, postoperative length of hospital stay, readmission rate, and mortality. RESULTS: Total hospital stay was significantly shorter among patients randomly assigned to enhanced recovery after surgery plus extended counseling (median 5 (range 2–29) days vs 7 (range 2–39) days, p < 0.001). The 2 treatment groups differed in adherence to the elements of postoperative enhanced recovery after surgery such as mobilization and total oral intake. The 2 treatment groups did not differ in overall, major, and minor morbidity; reoperation rate; readmission rate; and 30-day mortality. LIMITATIONS: The main limitation of this study was the absence of blinding. CONCLUSIONS: Perioperative information and guidance were important factors in enhanced recovery after surgery care and were associated with a significantly shorter length of hospital stay. Our findings suggest that perioperative counseling enables patients to comply with the elements of postoperative enhanced recovery after surgery and thereby reduces the length of hospital stay. This study was registered with ClinicalTrials.gov (NCT01610726). SeeVideo Abstract athttp://links.lww.com/DCR/A505 .